Serological reactions of the genus Peptostreptococcus. - Graham, M B (1978)
White male New Zealand rabbits were immunized with soluble antigen preparations (SP) of the following gram-positive anaerobic cocci: Peptostreptococcus anaerobius ATCC 27337 and VPI 5737; P. micros VPI 2618; Streptococcus morbillorum ATCC 27527; P. parvulus VPI 5229; and P. productus ATCC 27340. SP were reacted with homologous and heterologous rabbit antisera in immunodiffusion, immunoelectrophoresis, indirect fluorescent-antibody, and tanned-cell passive hemagglutination tests. Even though each antiserum reacted strongly with its homologous SP, no interspecies reactivity was observed except between P. productus antisera and P. parvulus SP by the passive hemagglutination test. Antisera prepared to both strains of P. anaerobius reacted with the other strain in all serological tests.